Evaluasi Penatalaksanaan Abortus Inkompletus di Rumah Sakit Y: Studi Retrospektif - Rosmiati, Rosmiati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Incomplete abortion is a pregnancy complication that requires prompt and appropriate management. Inadequate management can increase the risk of infection, bleeding, and secondary infertility. Therefore, evaluating the management of this case is crucial to improve the quality of obstetric care. Objective: To evaluate the management of incomplete abortion at Hospital Y based on standard operating procedures and patient clinical outcomes. Methods: This study used a retrospective study design with a descriptive-analytic approach. Medical records of patients with incomplete abortion from January 2023 to December 2024 were systematically analyzed. Results: Of the 120 incomplete abortion cases studied, 78% were managed with curettage, 15% with expectant management, and 7% with medication. Clinical outcomes showed that 92% of patients recovered without complications, while 8% experienced minor complications such as anemia and mild infection. Conclusion: The majority of incomplete abortion management at Hospital Y met obstetric care standards and resulted in good clinical outcomes. However, regular evaluation of the medical approach and expectations is needed to improve service effectiveness.